Independent Task Scheduling in Grid Computing Based on Queen Bee Algorithm - Zahra Pooranian; Mohammad Shojafar; Bahman Javadi (Institute of Advanced Engineering and Science, 2012)
The inherent dynamicity in grid computing has made it extremely difficult to come up with near-optimal solutions to efficiently schedule tasks in grids. Task Scheduling plays crucial role in Grid computing. It is a challengeable issue among scientists to achieve better results especially in makespan based on various AI methods. Nowadays, non deterministic algorithms provide better results for these tasks. In this study the task scheduling problem in Grid computing environments has been addressed. In this paper, Queen Bee Algorithm is used for resolving scheduling problem and the obtained results are compared with several Meta–heuristic Algorithms which are developed to solve the problem. As it illustrated, queen bee algorithm is declined considerably makespan and execution time parameters rather than others in different states.DOI: http://dx.doi.org/10.11591/ij-ai.v1i4.1229